Pemelajaran Kosakata Bahasa Indonesia bagi Penutur Asing: Adaptasi Pesantren - Shifa Fauziyah Renhoat; Itah Faitah; Nina Yunita; Ahmad Fadly (Jurnal Genre (Bahasa, Sastra, dan Pembelajarannya), 2020)
This study aims to provide an alternative offer of vocabulary learning models adapted from learning models in pesantren. Observations made during June 2019 and interviews with informants who have woven pesantren education and intruspection methods were applied in this study. In the pesantren environment, especially modern pesantren, vocabulary learning is done in a practical way. Speaking skills in the current context are focused on modern pesantren. In the pesantren tradition, especially traditional pesantren, vocabulary learning takes precedence over the strengthening of scientific terms, especially those contained in classical texts (kitab kuning). In the combination learning model, which is generally applied in semipesantren, the vocabulary learning is carried out on two lines: the classical and practical paths. This study offers the concept of learning on the basis of vocabulary mapping based on the needs and relationships between learners and BIPA teachers.